Investigaciones actuales y aplicaciones en la agroindustria del hongo Ganoderma lucidum - Paredes Leon, Christian Edgardo (2019)
This research work is focused on collecting scientific information regarding the latest research and applications in the Agroindustria of Ganoderma Lucidum, a medicinal mushroom in Asian culture. Since ancient times, fungi have been used as a raw material in the development of functional foods due to their medicinal properties. This research begins by providing relevant aspects such as their morphological characteristics, chemical composition, and the importance of its nutraceutical benefits, medicinal contributions for the benefit of the health and uses in agribusiness for the production of functional foods that, in addition to having pleasant characteristics for the consumer, give it an added value due to the nutritional properties that Ganoderma Lucidum possesses, important for the prevention and treatment of diseases. In addition, due to its nutraceutical properties, Ganoderma lucidum has a number of applications in the Agroindustria sector such as the production of beer, yogurts, cakes, coffee, dehydrated products, etc. So that they can take advantage of their medicinal qualities and give added value to the products without affecting their physical, chemical and organoleptic characteristics.